Nonuniform Polynomial Dichotomy for Noninvertible Linear Discrete-Time Systems in Banach Spaces - Tian Yue (Journal of Control Science and Engineering)
We study three polynomial dichotomy concepts for linear discrete-time systems in Banach spaces. Our main objective is to give characterizations in terms of Lyapunov functions for nonuniform polynomial dichotomy of nonautonomous and noninvertible linear discrete-time systems.